1998
DOI: 10.1002/aic.690440209
|View full text |Cite
|
Sign up to set email alerts
|

Defect‐free palladium membranes on porous stainless‐steel support

Abstract: Defect-pee Pd membranes were prepared by an electroless plating

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
151
0
9

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(174 citation statements)
references
References 31 publications
9
151
0
9
Order By: Relevance
“…Before surface modification, the PSS tubes were cleaned in an ultrasonic bath at 60 C and in an alkaline solution to remove any surface contaminants. The PSS tubes were then rinsed with isopropanol and left to dry overnight at 120 C. The exact compositions of solutions used during this study may be found in (Mardilovich et al 1998).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before surface modification, the PSS tubes were cleaned in an ultrasonic bath at 60 C and in an alkaline solution to remove any surface contaminants. The PSS tubes were then rinsed with isopropanol and left to dry overnight at 120 C. The exact compositions of solutions used during this study may be found in (Mardilovich et al 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Palladium was then deposited onto the PSS substrates using electroless plating. Details of the procedure can be found elsewhere (Mardilovich et al 1998). The dense Pd-based composite tube was heated to 500 C in helium at a rate of 1 C/min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…mL . L -1 ) was used as a reducing agent (Mardilovich et al, 1998). Two cycles of electroless plating were performed in order to achieve a highly selective and defect-free Pd membrane.…”
Section: Palladium Membrane Deposition By Electroless Platingmentioning
confidence: 99%
“…7 While the focus of metal hydride thin-fi lm research has been on the discovery of new material compositions, it can also be used to study the effect of doping, 8 interface energy, 9 and the elastic and plastic effects of clamping a nanomaterial to a matrix. 10 Besides hydrogen storage, metal hydrides are used in heat storage applications, 11 separation membranes, 12 hydrogen sensors, 13 and smart window applications. 14 , 15 Here, we focus on the last two applications.…”
Section: Introductionmentioning
confidence: 99%